OPTIMIZATION OF HYBRID PHOTOVOLTAIC THERMOELECTRIC GENERATOR SYSTEM FOR IMPROVING SOLAR PANEL EFFICIENCY - Faridah, Linda; Dicky Ramadhan, Sesep; Busaeri, Nundang (Institut Teknologi Nasional Yogyakarta, 2025)
The utilization of solar energy through photovoltaic (PV) technology continues to evolve as a promising renewable energy source. However, the efficiency of solar panels remains limited by heat generated during operation, causing performance degradation as temperature rises. This phenomenon presents a major challenge in optimizing PV technology. This research aims to enhance the efficiency of photovoltaic systems by incorporating Thermoelectric Generator (TEG) modules, resulting in an innovative hybrid Photovoltaic-Thermoelectric Generator (PV-TEG) system. The PV-TEG hybrid system is designed to harness excess heat produced by solar panels, which is then converted into additional electrical energy through TEG modules, utilizing the Seebeck effect. In this experimental study, two heat transfer methods were tested and compared: Micro-Channel Heat Pipe (MCHP) and copper plate. Both methods were evaluated to enhance the temperature gradient across the TEG modules, with the goal of optimizing the hybrid system's performance. The research methodology included design, fabrication, and testing of PV-TEG hybrid system prototypes under various controlled environmental conditions. Measured parameters included operational temperature, output voltage, current, and total power generated. Thermodynamic and electrical analyses were conducted to evaluate energy conversion efficiency and overall system performance. Test results showed that the PV-TEG hybrid system could increase overall efficiency by up to 10% compared to conventional solar panels. The use of copper plates as heat transfer media resulted in higher efficiency compared to MCHP, indicating greater potential for practical implementation. Economic analysis also demonstrated the long-term feasibility of this hybrid system, despite higher initial costs.In conclusion, the developed PV-TEG hybrid system makes a significant contribution to improving the energy efficiency of solar panels.